PİGMENTE DERİ LEZYONLARININ KLİNİK, DERMATOSKOPİK VE HİSTOPATOLOJİK KORELASYONU - DEMİR, BETÜL (Fırat Üniveristesi, 2009)
Dermatoskopi, pigmente deri lezyonların tanısında ve benign-malign ayırımının yapılmasında yaygın olarak kullanılmakta olan noninvazif bir yöntemdir. Bu çalışmada pigmente deri lezyonları klinik muayene, dermatoskopik ve histopatolojik inceleme yöntemleri ile değerlendirilerek lezyonların tanısı, melanositik-nonmelanositik ve benign-malign ayırımında klinik ve dermatoskopik muayenelerin sensitivite ve spesifitesinin araştırılması amaçlanmıştırÇalışmamız 2005-2006 yılları arasında Fırat Üniversitesi Hastanesi Dermatoloji polikliniğine başvuran 45 kadın ve 22 erkek toplam 67 hastada bulunan 94 adet pigmente deri lezyonunda yapıldı. Hastaların mevcut pigmente lezyonları klinik, dermatoskopik ve histopatolojik olarak incelendi. Lezyonların klinik, dermatoskopik ve histopatolojik tanıları karşılaştırıldı. İstatistiksel analizler için SPSS 12.0 paket programı kullanıldıLezyonların klinik ön tanıları ile dermatoskopik ön tanıları karşılaştırıldığında 73'ünün (%77.7), klinik ön tanıları ile histopatolojik tanıları karşılaştırıldığında 63'ünün, dermatoskopik ön tanıları ile histopatolojik tanıları karşılaştırıldığında ise 82'sinin (%87) birbiri ile uyumlu olduğu, melanositik nonmelanositik ayırımında klinik muayenenin istatistiksel olarak %96.6 sensitif ve %61.5 spesifik, dermatoskopinin ise %97.7 sensitif ve %88.8 spesifik olduğu, benign ile malign ayırımında klinik muayenenin istatistiksel olarak %92.4 sensitif ve %72.7 spesifik, dermatoskopinin ise %97.7 sensitif ve %80 spesifik olduğu saptandı.Sonuç olarak, dermatoskopi pigmente deri lezyonlarının doğru tanısında hekime yardımcıdır. Ayrıca dermatoskopi malign lezyonların erken tanısı ve eksizyonu prognozu açısından hastalara konfor sağlamaktadır. Ayrıca düşük riskli melanositik lezyonların gereksiz cerrahi müdahalesini engelleyerek hastaya ve hekime takip şansı sağlamaktadır.

Dermoscopy is a non-invasive method used in the diagnosis and benign-malignant differentiation of pigmented skin lesions. In this study, pigmented skin lesions were evaluated using methods of clinical, dermatoscopic and histopathologic examination. This evaluation was intended to investigate the sensitivity and specificity of clinical and dermatoscopic examinations in the diagnosis, as well as melanocytic-nonmelanocytic and benign-malignant differentiation of the pigmented skin lesions.The study was conducted on 94 pigmented skin lesions in a total of 67 patients, 45 females and 22 males, who presented at the Dermatology polyclinic of Fırat University Medical Center between 2005 and 2006 years. Pigmented lesions of the patients were examined clinically, dermatoscopically and histopathologically. Clinical, dermatoscopic and histopathologic diagnoses of the lesions were compared. SPSS 12.0 package software was used in the statistical analyses.When clinical and dermatoscopic pre-diagnoses of the lesions were compared, 73 (77.7%) were found consistent with one another; when clinical and histopathologic pre-diagnoses were compared, 63 (67%) were found consistent; and when dermatoscopic and histopathologic pre-diagnoses were compared, 82 (87%) were found consistent. Clinical examination was found statistically 96.6% sensitive and 61.5% specific, while dermoscopy was found 97.7% sensitive and 88.8% specific in the melanocytic-nonmelanocytic differentiation; and clinical examination was found statistically 92.4% sensitive and 72.7% specific, whereas dermoscopy was 97.7% sensitive and 80% specific in the benign-malignant differentiation.In conclusion, dermatoscopy helps the physician in accurate diagnosis of pigmented skin lesions. Otherwise dermoscopy enables a comfort to the patients in terms of early diagnosis and excision prognosis of malignant lesions. Furthermore, it prevents unnecessary surgical intervention in low-risk melanocytic lesions and provides a chance for follow-up to the physician and the patient.
Histopatholojic correlation of clinical and dermoscopic features in pigmented skin lesions
Keywords: Dermatoloji